2014
DOI: 10.14723/tmrsj.39.491
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of bio-oils produced by fast pyrolysis of bamboo

Abstract: Bamboo powder was analytically pyrolyzed using pyrolysis-gas chromatography (Py-GC), and the effects of fast pyrolysis conditions on the product distribution of bio-oil were evaluated. 4-Vinylphenol (4VP) was identified as a major product of bamboo fast pyrolysis by 1 H-NMR and 13 C-NMR spectrometry. The formation pathway of 4VP demonstrated that p-coumarate esters are present in bamboo lignin, and 4VP is likely to be derived from these p-coumarate structures. The evaluation of the effect of fast pyrolysis tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…There exists controversy in the identification of DHBF in lignin pyrolysis. , Qu et al and later Kato at al . have particularly found that GC/MS procedures can be misleading because of the closely resembling mass-spectroscopic spectra of DHBF and 4-vinylphenol ( 4VP ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There exists controversy in the identification of DHBF in lignin pyrolysis. , Qu et al and later Kato at al . have particularly found that GC/MS procedures can be misleading because of the closely resembling mass-spectroscopic spectra of DHBF and 4-vinylphenol ( 4VP ).…”
Section: Resultsmentioning
confidence: 99%
“…28,171 Qu et al 171 and later Kato at al. 28 have particularly found that GC/MS procedures can be misleading because of the closely resembling mass-spectroscopic spectra of DHBF and 4-vinylphenol (4VP). Furthermore, the isolation and reanalysis of this very major product using NMR and other methods allowed its identification as 4-vinylphenol.…”
Section: Channels Iia Ivb and Xmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, many researchers have studied the pyrolysis conversion of switch grass and have evaluated the obtained bio-oil with respect to its chemical composition (Charles et al, 2008), energy-conversion efficiency (Boateng et al, 2007), and effect of milling (Bridgman et al, 2007). Several studies on the pyrolysis conversion of crops other than switch grass, such as wheat straw (Fidalgo et al, 1993), rice husks (Gai et al, 2013), tobacco residue (Cardoso and Ataide, 2013), orange waste (Lopez-Velazquez et al, 2013), giant cane (Temiz et al, 2013), microalgae (Wang et al, 2013), and bamboo (Kato et al, 2014), have also been reported. These plants consist of cellulose, hemicellulose, and lignin.…”
Section: Introductionmentioning
confidence: 99%